A General Catalytic Hydroamidation of 1, 3‐Dienes: Atom‐Efficient Synthesis of N‐Allyl Heterocycles, Amides, and Sulfonamides1. Issue 6 (22nd January 2014) - Banerjee, Debasis; Junge, Kathrin; Beller, Matthias
Abstract Transition‐metal‐catalyzed hydroamination reactions are sustainable and atom‐economical CN bond‐forming processes. Although remarkable progress has been made in the inter‐ and intramolecular amination of olefins and 1, 3‐dienes, related intermolecular reactions of amides are still much less known. Control of the regioselectivity without analogous telomerization is the particular challenge in the catalytic hydroamidation of alkenes and 1, 3‐dienes. Herein, we report a general protocol for the hydroamidation of electron‐deficient N‐heterocyclic amides and sulfonamides with 1, 3‐dienes and vinyl pyridines in the presence of a catalyst derived from [{Pd(π‐cinnamyl)Cl}2] and ligand L7 or L10. The reactions proceeded in good to excellent yield with high regioselectivity. The practical utility of our method is demonstrated by the hydroamidation of functionalized biologically active substrates. The high regioselectivity for linear amide products makes the procedure useful for the synthesis of a variety of allylic amides.